Accessory and cavitated uterine masses: a case series and review of the literature - Dekkiche, S.; Dubruc, E.; Kanbar, M.; Feki, A.; Mueller, M.; Meuwly, J-Y.; Mathevet, P. (Frontiers in Reproductive Health, 2023)
Objectives The purpose of this study is to report nine patients of young women who underwent a surgical treatment of an accessory and cavitated uterine mass (ACUM) in our hospital between 2014 and 2022 and review all cases described in the literature. Material and methods The principal outcomes measured are the imaging techniques used to determine the diagnosis, the type of surgery used and the post-operative evolution of symptoms. We also report and analyse the 79 patients found in the literature since 1996 in addition to our 9 patients. Results Surgical excision is the only long-lasting treatment. Small invasive surgery with laparoscopic access is the gold standard and most widely used (83.0%). Some new therapeutic procedures have been recently described of which ethanol sclerotherapy seems very promising. Post-operatively, 54.5% of patients have a complete relief of symptoms. MRI is the best imaging technique to identify ACUM. Finally, we refine the description of this pathology and give a more precise definition of it. Conclusion Through our literature review and the analysis of our cases, we want to underline an important diagnostic criterion of this pathology: the fallopian tube on the homolateral side of the ACUM never communicates with the latter. It is a capital element for differential diagnosis.